Discovering Psalms: content, interpretation, reception - Creach, Jerome F. D. (Discovering biblical texts, 2020)
This compact introduction to the interpretation of the book of Psalms encourages in-depth study of the text and genuine grappling with related theological and historical questions by providing a critical assessment of key interpreters and interpretative debates. It draws on a range of methodological approaches (author-, text-, and reader-centered) and reflects the growing scholarly attention to the reception history of biblical texts, increasingly viewed as a vital aspect of interpretation rather than an optional extra